The biochemical subtype is a predictor for cognitive function in glutaric aciduria type 1: a national prospective follow-up study - Märtner, E.M. Charlotte; Thimm, Eva; Guder, Philipp; Schiergens, Katharina A.; Rutsch, Frank; Roloff, Sylvia; Marquardt, Iris; Das, Anibh M.; Freisinger, Peter; Grünert, Sarah; Krämer, Johannes; Baumgartner, Matthias R.; et al. (Scientific reports, 2021)
The aim of the study was a systematic evaluation of cognitive development in individuals with glutaric aciduria type 1 (GA1), a rare neurometabolic disorder, identified by newborn screening in Germany. This national, prospective, observational, multi-centre study includes 107 individuals with confirmed GA1 identified by newborn screening between 1999 and 2020 in Germany. Clinical status, development, and IQ were assessed using standardized tests. Impact of interventional and non-interventional parameters on cognitive outcome was evaluated. The majority of tested individuals (n = 72) showed stable IQ values with age (n = 56 with IQ test; median test age 11 years) but a significantly lower performance (median [IQR] IQ 87 [78-98]) than in general population, particularly in individuals with a biochemical high excreter phenotype (84 [75-96]) compared to the low excreter group (98 [92-105]; p = 0.0164). For all patients, IQ results were homogenous on subscale levels. Sex, clinical motor phenotype and quality of metabolic treatment had no impact on cognitive functions. Long-term neurologic outcome in GA1 involves both motor and cognitive functions. The biochemical high excreter phenotype is the major risk factor for cognitive impairment while cognitive functions do not appear to be impacted by current therapy and striatal damage. These findings implicate the necessity of new treatment concepts.
Verlagskorrektur erschienen am 12. Oktober 2021 mit dem DOI 10.1038/s41598-021-00137-5 wegen falscher Affiliationsangabe für Herrn Nikolas Boy
Gesehen am 26.11.2021